2011
DOI: 10.1007/s11071-011-0038-y
|View full text |Cite
|
Sign up to set email alerts
|

Bistability of curved microbeams actuated by fringing electrostatic fields

Abstract: In this work we investigate the feasibility of two-directional switching of an initially curved or pre-buckled electrostatically actuated microbeams using a single electrode fabricated from the same structural layer. The distributed electrostatic force, which is engendered by the asymmetry of the fringing fields in the deformed state, acts in the direction opposite to the deflection of the beam and can be effectively viewed as a reaction of a nonlinear elastic foundation with stiffness parameterized by the vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
63
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(65 citation statements)
references
References 55 publications
1
63
0
1
Order By: Relevance
“…Krylov et al [13][14][15] examined experimentally and theoretically the various scenarios of snap-through motion and pull-in instability in deliberately fabricated MEMS arches of deep capacitive gaps. They used the Galerkin procedure to solve for the dynamic response including geometric and electric nonlinearities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Krylov et al [13][14][15] examined experimentally and theoretically the various scenarios of snap-through motion and pull-in instability in deliberately fabricated MEMS arches of deep capacitive gaps. They used the Galerkin procedure to solve for the dynamic response including geometric and electric nonlinearities.…”
Section: Introductionmentioning
confidence: 99%
“…They also studied the transient response and escape from one potential well to the other one. In [15], Krylov et al demonstrated the actuation of clamped-clamped arches using fringing effect of the electrostatic forces.…”
Section: Introductionmentioning
confidence: 99%
“…The main problem with this approach is that the distributed electrostatic force comes in an integral form in the resulting ROM equations, and consequently this integral form is not easy to deal analytically due to nonlinearities arising from its denominator. As an attempt to overcome this challenge, some groups [31,32] used Taylor-series expansion procedure, which brings the nonlinearity to the numerator of the electrostatic force and hence simplifies the calculation of nonlinear ROM integrals. Others suggested multiplying the resultant equation of motion by the electrostatic force denominator and hence the evaluation of the integral in the ROM equation will not be problematic anymore [25].…”
Section: Static Analysismentioning
confidence: 99%
“…In particular, curved micro-beams tend to unveil snap-through instabilities and symmetric/nonsymmetric buckling behaviors. [23][24][25][26][27][28][29][30][31][32][33] In this article, the influence of SQFD on oscillations of a slightly curved micro-beam is considered. The initial shape of the beam is assumed to have a sinusoidal profile.…”
Section: Introductionmentioning
confidence: 99%